RANCANG BANGUN SISTEM MONITORING SUHU DAN KELEMBABAN PADA RUANG SERVER BERBASIS IoT (INTERNET OF THINGS) - Santoso, Gatot; Kristiyana, Samuel; Hani, Slamet; Mujahidin, Achmad Miradani (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2019)
Room server is a room that is used to store server computers and network devices. Room server is important assets for companies or institutions that implement information technology as a support in their daily activities. The importance of that is because in the server room there are applications and databases that store all important and valuable information for the company or institution concerned, therefore the server room must always be in good condition. Design of temperature and humidity monitoring systemsis designed to detect changes in temperature and humidity in the room using ESP8266 Node MCU as the main control, then use DHT 11 as a temperature and humidity detection sensor, then the data will be sent to the Telegram application already installed on the smartphone and displayed in the LCD. If the MQ-2 gas sensor detects a smoke greater than 500 ppm, the buzzer active. With this tool, it is expected to be able to monitor the real time room temperature and humidity in the server room so that it can reduce the damage to the hard drive or other damage.